Qualität und Objektivierbarkeit der Aus- und Weiterbildung in der Urologie - Müller, Stefan C.; Strunk, Timo; Alken, Peter (Der Urologe, 2012)
The attraction to study medicine has not changed, however we are facing a lack of trainees especially in surgical subspecialties like urology. Possible explanations are a 70% proportion of female students and different views on the work-life balance in the future. A high burden of theory and unrealistic multiple choice examinations support those who can learn but there are no objective and reproducible criteria to recognize the competence of a good physician early in the career. This problem continues during residency, especially in surgical subspecialities. The different medical boards in Germany responsible for the training programs have no concepts. Many attempts in other countries to objectively measure surgical skills have so far been ignored. If we do not want to lose our traditionally high competence in medicine we should join those who attempt to improve teaching and to use methods for selecting suitable candidates for surgery as soon and as objectively as possible.